Macroeconomic Modeling in Post-pandemic Times - Anton I. Votinov1; Julia A. Polshchikova; Karen A. Nersisyan (Финансовый журнал)
Recent trends in the global world (the financial and coronavirus crises, global geopolitical uncertainty, etc.) put macroeconomic modeling in front of the need to consider crisis phenomena in models. In this paper we try to answer the question of what has changed in macroeconomic modeling due to the coronavirus crisis and other shocks that the global economy has faced recently. Based on the literature review, the current directions in the implementation of the main classes of macroeconomic models in the pandemic and post-pandemic periods are examined. First, approaches to forecasting in crisis conditions are analyzed. Then the emphasis is shifted to nowcasting and projections for short periods of time. Mathematical chaos theory is also considered in the context of forecasting under specific and large shocks. We also discuss general equilibrium models and the relevance of incorporating heterogeneity and epidemiologic concepts into the structure of such models. Finally, we point out to a multiscenario approach to analyzing fiscal sustainability through models in the context of the unprecedented increase of government burdens faced by many countries during crisis.